Physical activity and depressive symptoms among Chinese university students: Grit as a mediator - Yizhou Chen; Jie Zhang (PLoS ONE, 2026)
Background While physical activity is widely recognized for its protective role against depressive symptoms, the specific psychological mechanisms that explain this relationship, particularly among Chinese university students, require further exploration. The present study seeks to clarify whether grit as a hypothesized mediator explaining how physical activity is linked to depressive symptoms severity within this population. Methods In this cross-sectional investigation, 3,140 Chinese university students were recruited to complete an online survey. Assessments included demographic variables, physical activity levels, grit, and depressive symptoms, each measured with validated instruments. The hypothesized mediation pathway—wherein grit serves as the mediating variable—was tested via the PROCESS macro for SPSS, with bias-corrected bootstrapping (5,000 resamples) used to assess the indirect effect. Results Analyses demonstrated a significant negative association between physical activity and depressive symptoms. Crucially, grit was found to completely mediate this association. The indirect pathway through grit was statistically significant ( ab = −0.013, 95% CI [−0.016, −0.010]), whereas the direct effect of physical activity was non-significant ( c’ = −0.002, p > 0.05, 95% CI [−0.011, 0.007]). Conclusions These findings indicate that the beneficial effect of physical activity on depressive symptoms is primarily channeled through grit. Intervention strategies aimed at improving mental well-being in this population may be more effective if they combine physical activity promotion with grit-fostering components.